Gestión de control contable de los ingresos en empresas PYMES del sector de construcción - Solari Dávila, Angel Jamil (2021)
The present study called, "MANAGEMENT OF ACCOUNTING CONTROL OF INCOME IN SME COMPANIES OF THE CONSTRUCTION SECTOR", aimed to analyze the management of accounting control of income in SMEs of the Construction Sector and how these affect the reasonableness of the financial statements, which was developed based on a methodological process, which began with the identification of the mixed approach, as well as the type of investigation, this being the descriptive one, where the current situation of the processes was analyzed, diagnosed and interpreted maintained by companies in the construction sector, identifying factors that influence the verification process with the reality of the balances in the statement of comprehensive income of the company, for this, a research instrument was applied, being the interview, itself that helped to collect information, the same that generated results focused on the management of accounting control, being dispensable better pray the presentation of the Financial Statements of the companies focused on the construction area, as well as immediately register all their income and expenses originated in the fiscal period, because a delay of the same, can harm the administrative and organizational competitiveness of the company........